Swine Enteric Colibacillosis in Spain: Pathogenic Potential of mcr-1 ST10 and ST131 E. coli Isolates - García-Meniño, Isidro; García, Vanesa; Mora, Azucena; Díaz-Jiménez, Dafne; Flament-Simon, Saskia C.; Alonso, María Pilar; Blanco, Jesús E.; Blanco, Miguel; Blanco, Jorge (Frontiers in Microbiology, 2018)
This is a wide epidemiological study of 499 E. coli isolates recovered from 179 outbreaks of enteric colibacillosis from pig production farms in Spain during a period of 10 years. Most samples were of diarrheagenic cases occurred during the post wean period (PWD) which showed to be significantly associated with ETEC (67%) followed by aEPEC (21.7%). On the contrary, aEPEC was more prevalent (60.3%) among diarrheas of suckling piglets, followed by ETEC (38.8%). STEC/ETEC or STEC were recovered in 11.3% and 0.9% of PWD and neonatal diarrhea, respectively. Detection of the F4 colonization factor was not significantly different between isolates recovered from neonatal pigs and those recovered post wean (40.5% versus 27.7%) while F18 was only present among PWD isolates (51.5% of ETEC, STEC and STEC/ETEC isolates). We also found a high prevalence of resistance to colistin related to the presence of the mcr-1 gene (25.6% of the diarreagenic isolates). The characterization of 65 representative mcr-1 isolates showed that all were phenotypically resistant to colistin (> 2 µg/ml), and most (61 of 65) multidrug-resistant (MDR). Six ETEC and 1 STEC mcr-1 isolates were also carriers of ESBL genes. In addition, other 7 mcr-1 isolates harbored mcr-4 (3 ETEC) and mcr-5 (2 ETEC and 2 aEPEC) genes. In the phylogenetic analysis of the 65 mcr-1 diarrheagenic isolates we found that more than 50% (38 out of 65) belonged to A-ST10 Cplx and from those, 29 isolates showed the clonotype CH11-24. In this study, we also recovered 18 ST131 isolates including 7 mcr-1 carriers. To the best of our knowledge, this would be the first report of ST131 mcr-1 isolation in pigs. Worryingly, the swine mcr-1 ST131 carriers also showed MDR, including to trimethoprim-sulfamethoxazole, tobramycin, gentamicin and ciprofloxacin. In the PFGE-macrorestriction comparison of clinical swine and human ST131, we found high similarities (≥ 85%) between 2 pig and 2 human ST131 isolates of virotype D5. Acquisition of mcr-1 by this specific clone means an increased risk due to its special feature of congregating virulence and resistance traits, together with its spread capability. Here we show a potential zoonotic swine source of ST131.